The Effect of Smartphone Addiction on Quality of Sleep Among Nursing Students in Medical Faculty Udayana University - Sinta Febrina, Ni Made; Ayu Suarningsih, Ni Kadek; Nurhesti, Putu Oka Yuli (Journal of A Sustainable Global South; Vol 6 No 2 (2022): August 2022, 2022)
Abstract Sleep quality is a complex phenomenon that is difficult to measure objectively in individuals. Nursing students become one of the groups that are susceptible to decreased sleep quality. This is due to the many demands that students must do in their daily lives. Nowadays, changes in students lifestyles that lead to the use of massive technology, such as smartphones can have an impact on the quality of sleep. Indirectly, the convenience provided by smartphones gives an addiction effect to users. The purpose of this study was to determine the differences between quality of sleep in nursing students at Medical Faculty, Udayana University based on the level of smartphone addiction. This research is a descriptive study with a cross-sectional approach. The sample size was 123 students obtained from the use of sampling techniques of proportionate stratified random sampling. The results of this study indicate that as many as 51.2% of students are at a high smartphone addiction level. Also, 84.6% of students have poor sleep quality. The Mann Whitney statistical test results obtained p-value 0.01 <0.05, which means that there is a significant difference between the quality of sleep in nursing students at Faculty of Medicine Udayana University based on the level of smartphone addiction. This tudy suggest that students will be able to be wiser and more self-controlled in smartphone use on their daily lives to minimize the impact of smartphone addiction.   Keywords: Nursing Student, Sleep Quality, Smartphone Addiction